2022
DOI: 10.1097/aud.0000000000001256
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Training of Spatial Hearing Promotes Auditory Abilities of Bilateral Cochlear Implant Adults: A Pilot Study

Abstract: Objective: The aim of this study was to evaluate the feasibility of a virtual reality-based spatial hearing training protocol in bilateral cochlear implant (CI) users and to provide pilot data on the impact of this training on different qualities of hearing. Design: Twelve bilateral CI adults aged between 19 and 69 followed an intensive 10-week rehabilitation program comprised eight virtual reality training sessions (two per week) interspersed with several evaluation sessions (2 weeks before training started… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 75 publications
0
8
0
3
Order By: Relevance
“…This effect of multisensory training on unisensory experience was also found in adult patients with bilateral cochlear implants (BCIs); a study by [ 22 ] showed faster improvement after multisensory spatial training compared to training in the auditory modality only. Although both populations (UHL and BCIs) have different adaptation strategies, they both rely on visual sensory inputs to optimize environmental spatial mapping [ 25 ].…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…This effect of multisensory training on unisensory experience was also found in adult patients with bilateral cochlear implants (BCIs); a study by [ 22 ] showed faster improvement after multisensory spatial training compared to training in the auditory modality only. Although both populations (UHL and BCIs) have different adaptation strategies, they both rely on visual sensory inputs to optimize environmental spatial mapping [ 25 ].…”
Section: Discussionmentioning
confidence: 66%
“…Anatomically, this can be explained by the presence of direct projections originating from the representation of the peripheral visual fields in the pre-striate cortex [ 20 ] towards the caudal areas of the auditory cortex, which are involved in spatial processing [ 21 ]. A large body of studies proved that multisensory stimulation that includes visual feedback is more effective than unisensory stimulation in normal-hearing participants with monaural plugs [ 15 , 16 , 18 , 22 ] and in patients with cochlear implants [ 17 , 23 ]. The study of [ 15 ] suggests that unisensory auditory training, applied to normal-hearing participants with ear plugs, showed no improvement in spatial behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multimodal training protocols have been developed 17 to enhance the spatial hearing abilities of CI users. While attending these protocols, patients are encouraged to actively explore the environment, as movements enrich the incoming auditory information about space.…”
Section: Introductionmentioning
confidence: 99%